Estimating elastic properties and attenuation factor from different frequency components of observed seismic data. Issue 2 (21st October 2019) - Chen, Huaizhen
SUMMARY: Based on an attenuation model, we first express frequency-dependent P - and S -wave attenuation factors as a function of P -wave maximum attenuation factor, and then we re-express P - and S -wave velocities in anelastic media and derive frequency-dependent stiffness parameters in terms of P -wave maximum attenuation factor. Using the derived stiffness parameters, we propose frequency-dependent reflection coefficient in terms of P - and S -wave moduli at critical frequency and P -wave maximum attenuation factor for the case of an interface separating two attenuating media. Based on the derived reflection coefficient, we establish an approach to utilize different frequency components of observed seismic data to estimate elastic properties ( P - and S -wave moduli and density) and attenuation factor, and following a Bayesian framework, we construct the objective function and an iterative method is employed to solve the inversion problem. Tests on synthetic data confirm that the proposed approach makes a stable and robust estimation of unknown parameters in the case of seismic data containing a moderate noise/error. Applying the proposed approach to a real data set illustrates that a reliable attenuation factor is obtained from observed seismic data, and the ability of distinguishing oil-bearing reservoirs is improved combining the estimated elastic properties and P -wave attenuation factor.